The sunk cost bias and managerial pricing practices - Nabil Al-Najjar; Sandeep Baliga; David Besanko (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2005)
This paper provides an explanation for why the sunk cost bias persists among firms in a competitive environment in which rich learning possibilities are allowed. We envision firms that experiment with cost methodologies that are consistent with real-world accounting practices, including ones that confuse the relevance of variable, fixed, and sunk costs to pricing decisions. Firms follow 'naive' adaptive learning to adjust prices and reinforcement learning to modify their costing methodologies. Costing and pricing practices that increase profits are reinforced. We show that all firms eventually display the sunk cost bias in their pricing behavior.
Keywords: 330